The Influence of the Current Ratio and Debt to Asset Ratio on Firm Value at PT Surya Semesta Internusa Tbk - Bulan Oktrima (Formosa Journal of Multidisciplinary Research, 2024)
The results of this research aim to reveal several things, namely, to determine the influence of the Current Ratio (CR), Debt to Asset Ratio (DAR)) on Firm Value (Tobin's Q), with partial and simultaneous Firm Value (Tobin's Q) at PT Surya Semesta Internusa Tbk for the 2009-2019 period. The nature of this research is quantitative descriptive. using secondary data, with the classic Asumi test and the method used to test and analyze the influence partially and simultaneously is by using the correlation coefficient test, coefficient of determination test, and hypothesis testing, namely the t test and f test. Testing the Current Ratio (CR) hypothesis does not have a significant effect on the Firm Value (Tobin's Q) at PT Surya Semesta Internusa Tbk for the 2009 - 2019 period. The results of the T test show that Tcount is 0.684 with a comparison of Ttable of 1.860. The significant value is 0.514 > 0.05 then it can be concluded that Ho1 is accepted and Ha1 is rejected. Debt to Asset Ratio (DAR) has a positive and insignificant effect on Firm Value (Tobin's Q) at PT Surya Semesta Internusa Tbk for the 2009 - 2019 period. The results of the T test show that Tcount is 2.134 as large as the Ttable ratio of 1.860. As for the significant value of 0.065 > 0.05, it can be concluded that Ho2 is accepted and Ha2 is rejected. Current Ratio (CR) and Debt to Asset Ratio (DAR) together do not have simultaneous a significant effect on Firm Value (Tobin's Q) at PT Surya Semesta Internusa Tbk. The results of the F test show that Fcount is 2.376 with a comparison of Ftable of 4.460. As for the significant value of 0.155 > 0.05, it can be concluded that Ho3 is accepted and Ha3 is rejected. Y=0.126 – 0.106X1 + 1.331X2.